English Language Learner Classmates and the Classroom Social Skills of Students with Disabilities. Issue 7 (July 2015) - Gottfried, Michael A.; Polikoff, Morgan S.
Background/Context: Though the development of social skills in kindergarten is critical, a research gap exists in how the context of the general education classroom may influence the social skills outcomes of students with disabilities: None have considered the role of peer effects in this domain. This gap is critical to address, as multiple high-needs groups are increasingly present in the same general education classroom settings. Purpose/Objective: This study asks two key research questions: (1) In kindergarten, to what extent do the classroom social skills outcomes of children with disabilities differ based on the number of ELL classmates? (2) In kindergarten, to what extent do the classroom social skills outcomes of ELL students differ based on the number of classmates with disabilities? Population/Participants: The data are sourced from the Early Childhood Longitudinal Study-Kindergarten Class (ECLS-K), which is a nationally representative sample of students, teachers, and schools. Information was first collected from kindergartners (as well as parents, teachers, and school administrators) from U.S. kindergarten programs. This study utilizes data collected at the fall and spring of kindergarten. Research Design: This study combines secondary data analyses and quasi-experimental methods. There are three social skills outcomes: (1) approaches to learning, (2) interpersonal skills, and (3) self control. The study begins with a baseline, linear regression model. To address issues pertaining to omitted variable bias, the study employs multilevel fixed effects modeling. Findings: The coefficients indicate that students with disabilities tend to have improved social skills with an increase in the number of ELL classmates. The effects remain significant even after accounting for multiple omitted variable biases. Notably, the reverse relationship does not hold: The number of classmates with disabilities has no significant influence on the outcomes of ELL students. Conclusions/Recommendations: This research offers more in-depth insight into how the classroom context and the effects of classmates may have a unique relationship for specific high-needs groups such as students with disabilities—a strand of research in this area that is often overlooked. School practices can thus be guided by determining not simply if one group of students performs better or worse on average, but rather by asking, better or worse for whom in particular?